A simple model of income, aggregate demand, and the process of credit creation by private banks - Giovanni Bernardo; Emanuele Campiglio (Levy Economics Institute of Bard College, 2013)
This paper presents a small macroeconomic model describing the main mechanisms of the process of credit creation by the private banking system. The model is composed of a core unit - where the dynamics of income, credit, and aggregate demand are determined - and a set of sectoral accounts that ensure its stock-flow consistency. In order to grasp the role of credit and banks in the functioning of the economic system, we make an explicit distinction between planned and realized variables, thanks to which, while maintaining the ex-post accounting consistency, we are able to introduce an ex-ante wedge between current aggregate income and planned expenditure. Private banks are the only economic agents capable of filling this gap through the creation of new credit. Through the use of numerical simulation, we discuss the link between credit creation and the expansion of economic activity, also contributing to a recent academic debate on the relation between income, debt, and aggregate demand.
Keywords: E20; E51; G21; O42; 330; Banking System; Credit Creation; Growth; Aggregate Demand; Macroeconomic Modeling